Integrated Glycome Strategy for Characterization of Aberrant LacNAc Contained N-Glycans Associated With Gastric Carcinoma - Hanjie Yu (Frontiers in Oncology, 2019)
Aberrant glycosylation is not only a feature of malignant cell transformation, but also plays an important role in metastasis. In the present study, an integrated strategy combining the lectin microarrays and lectin cytochemistry was employed to investigate and verify the altered glycopatterns in gastric cancer (GC) cell lines as well as resected tumor specimens from matched tissue sets of 46 GC patients. Subsequently, lectin-mediated affinity capture glycoproteins, and MALDI-TOF/TOF-MS were employed to further acquire precise structural information of the altered glycans. According to the results, the glycopatterns recognized by 10 (e.g., ACA, MAL-I, and ConA) and 3 lectins (PNA, MAL-I, and VVA) showed significantly variations in GC cells and tissue compared to their corresponding controls, respectively. Notably, the relative abundance of Galβ-1,4GlcNAc (LacNAc) recognized by MAL-I exhibited a significant increase in GC cells (p < 0.001) and tissue from patients at stage II and III (p < 0.05), and a significant increase in lymph node positive tumor cases, compared with lymph node negative tumor cases (p < 0.05). More LacNAc contained N-glycans were characterized in tumor sample with advanced stage compared to corresponding control. Moreover, there were 10 neo-LacNAc-contained N-glycans (e.g., m/z 1625.605, 1803.652, and 1914.671) only presented in GC tissue with advanced stage. Among these, six N-glycans were modified with sialic acid or fucose based on LacNAc to form sialylated N-glycans or lewis antigens, respectively. Our results revealed that the aberrant expression of LacNAc is a characteristic of GC, and LacNAc may serve as a scaffold to be further modified with sialic acid or fucose. Our findings provided useful information for us to understand the development of GC.